El discurso poético mapuche y su vinculación con los “temas de resistencia cultural” - García Barrera, Mabel (Revista Chilena de Literatura, 2006)
This work studies the discursive and rhetorical strategies adopted by the current Mapuche poetical discourse deriving from a process of cultural resistance, by examining them in theworks of Rayen Kuyen, Bernardo Colipán, Graciela Huinao, and César Millahuaique. It posits that these strategies are inscribed in the Mapuche discourse as an answer to a continued dialogue maintained by the cultural memory and the hegemonic discourse of the western culture, and whose origin dates back to the colonial discourse.